Analysis of Clean Water Distribution Pipe Network PDAM Way Rilau Using Epanet 2.2 Software (Case Study: District Meter Area G26) - Jalal, Muhammad Agung Wijdan; Zakaria, Ahmad; Ashruri, Ashruri; Wahono, Endro P. (Journal of Engineering and Scientific Research, 2025)
As the population continues to grow, the demand for clean water has risen significantly, requiring Regional Drinking Water Companies (PDAMs) to ensure optimal service by maintaining quality, quantity, and continuity. This study focuses on projecting the clean water demand for PDAM Way Rilau in the DMA G26 service area of Sukabumi Village over the next 20 years, based on current customer data, while also evaluating the adequacy of its production capacity through 2044. Additionally, the research includes a simulation and assessment of the existing water distribution network in 2024 using Epanet version 2.2. The methodology involves projecting customer growth using arithmetic, geometric, and exponential models, followed by calculations of future water demand and analysis of the pipeline system. Results indicate that the projected maximum daily water demand in 2044 will reach 603,245 liters per day (6.982 L/s), while the current production capacity of 1,143,936 liters per day (13.24 L/s) is adequate for long-term needs. However, Epanet simulations identified several technical issues, such as low pressure at nodes J372 and J370, high headloss in pipe Pi356, and below-standard flow velocity in 13 pipes. These issues were addressed by adjusting pipe diameters and increasing reservoir head, resulting in improved network performance under both normal and peak conditions.